Heterologous Secretory Expression and Characterization of Dimerized Bone Morphogenetic Protein 2 in Bacillus subtilis. (23rd November 2017) - Hanif, Muhammad Umair; Gul, Roquyya; Hanif, Muhammad Imran; Hashmi, Abid Ali
Abstract : Recombinant human Bone Morphogenetic Protein 2 (rhBMP2) has important applications in the spine fusion and ortho/maxillofacial surgeries. Here we first report the secretory expression of biological active dimerized rhBMP2 from Bacillus subtilis system. The mature domain of BMP2 gene was amplified from pTz57R/BMP2 plasmid. By using pHT43 expression vector two constructs, pHT43-BMP2-M (single BMP2 gene) and pHT43-BMP2-D (two BMP2 genes coupled with a linker to produce a dimer), were designed. After primary cloning (DH5 α strain) and sequence analysis, constructs were transformed into Bacillus subtilis for secretory expression. Expression conditions like media (2xYT) and temperature (30°C) were optimized. Maximum 35% and 25% secretory expression of monomer ( 13 kDa) and dimer ( 25 kDa), respectively, were observed on SDS-PAGE in SCK6 strain. The expression and dimeric nature of rhBMP2 were confirmed by western blot and native PAGE analysis. For rhBMP2 purification, 200 ml culture supernatant was freeze dried to 10 ml and dialyzed (Tris-Cl, pH 8.5) and Fast Protein Liquid Chromatography (6 ml, Resource Q column) was performed. The rhBMP2 monomer and dimer were eluted at 0.9 M and 0.6 M NaCl, respectively. The alkaline phosphatase assay of rhBMP2 (0, 50, 100, 200, and 400 ng/ml) was analyzed on C2C12 cells and maximum 200 ng/ml activity was observed in dose dependent manner.